2017
DOI: 10.1080/14756366.2016.1238367
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioactivity of several new hetaryl sulfonamides

Abstract: Abstract1-(4-Methylsulfonyl)-2-thione-4-aryl-5-Z-6-methyl and oxyalkyl-imidazoles were synthesized from different tetrahydropyrimidinethiones and aryl sulfonyl chloride. These compunds were tested for metal chelating effects and to determine the phrase in which inhibition occured between two physiologically pertinent compunds and carbonic anhydrase (CA) isozymes I and II (hCA I and II), butyrylcholinesterase (BChE) and acetylcholinesterase (AChE). AChE was detected in high concentrations in the brain and red b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 78 publications
1
57
0
Order By: Relevance
“…Human CA I is found at high concentrations in the blood and gastrointestinal tract and it can be expressed in almost all tissues . It has been associated with diseases such as epileptic seizure, idiopathic intracranial hypertension, central sleep apnea, cystinuria, periodic paralysis, and dural ectasia .…”
Section: Discussionsupporting
confidence: 78%
“…Human CA I is found at high concentrations in the blood and gastrointestinal tract and it can be expressed in almost all tissues . It has been associated with diseases such as epileptic seizure, idiopathic intracranial hypertension, central sleep apnea, cystinuria, periodic paralysis, and dural ectasia .…”
Section: Discussionsupporting
confidence: 78%
“…Two isoenzymes are mitochondrial (CAs VA and VB), five are cytosolic (CAs I, II, III, VII, and XIII), four are membrane bound (CAs IV, IX, XII and XIV), and one is secreted (CA VI). [21][22][23][24] Additionally, the butyrylcholinesterase enzyme (BChE), which is considered as pseudocholinesterase (ChE) The CA is an extremely efficacious catalyst of reversible interconversion of CO 2 and HCO − 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It catalysis the separation of CO 2 to HCO 3 − and the corresponding dehydration of HCO 3 − in acidic position with regeneration of CO 2 . [20][21][22] Diabetes is defined as a general health difficulty, affecting humans in both developing and developed countries, with no disagreement of race. [18] Additionally, recent investigations showed that acetylcholinesterase inhibitors (AChEIs) not only reduce the cognitive deficiency of AD patients by increasing acetylcholine amounts, but also act as disease improving factors by hampering the early stage of AD, the assembly of -amyloid peptide into amyloid plaque.…”
Section: Introductionmentioning
confidence: 99%